DESKRIPSI HASIL JAWABAN SISWA MAN 2 BEKASI DALAM MENYELESAIKAN PERSOALAN TRIGONOMETRI DITINJAU DARI KEMAMPUAN REPRESENTASI MATEMATIKA - R. Radiusman; Harry Soeprianto; Maslina Simanjuntak (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2020)
This qualitative descriptive study aims to describe the students' mathematical representation ability in solving trigonometric problems. This research was conducted in class X IPA 1 MAN 2 Bekasi City totaling 39 people. Data in this study were obtained through the results of student answers and interviews. The mathematical representation is given consists of two questions in the form of description. The subject of this study consisted of one student and the research data were analyzed using qualitative descriptive techniques. The results showed that the research subjects were able to choose, translate mathematical problems and the research subjects were able to use ideas into model form to describe mathematical phenomena but the inability to understand the trigonometric comparison formula became the cause of the research subjects being unable to solve mathematical problems properly.